Influence of servant leadership and volunteer motivation on the satisfaction of Covid-19 task force volunteer - Immanuel Mu'ammal; Risky Angga Pramuja (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2022)
The COVID-19 pandemic has made managing volunteers in non-profit organizations even more difficult, especially managing volunteers on the front lines. For maximum performance, the leader's role is needed to provide job satisfaction to them. In addition, volunteer satisfaction at work is also determined by how much motivation they have to serve the community. This study examines the relationship between servant leadership style and volunteer inspiration on volunteer satisfaction. The data was obtained by distributing questionnaires to 144 covid-19-task forces called MAHARESIGANA. The influence relationship between variables was analyzed using WARP-PLS 7. This study's results indicate a positive and significant relationship between servant leadership and volunteer satisfaction. The relationship between volunteer motivation and satisfaction also shows a positive and significant value.